Clinical efficacy of the combined use of two medicinal forms of recombinant interferon α -2b in the treatment of infectious mononucleosis in children - G. P. Martynova; L. A. Ikkes; Ya. A. Bogvilena (Детские инфекции (Москва), 2019)
Justify the need to include two medicinal forms of recombinant interferon α -2b in combination with highly active antioxidants vitamins E and C (VIFERON®) in the form of rectal suppositories and gel for external use in the treatment of infectious mononucleosis in children.A clinical and laboratory examination of 115 children with infectious mononucleosis aged 3 to 11 years was carried out. Depending on the treatment, the patients were divided into three groups: the first group consisted of 50 children who received combination therapy with recombinant interferon α -2b (rIFN- α -2b, VIFERON®) in the acute period of the disease in the form of rectal suppositories and a gel for external use . The second group of children (35 people) received only rIFN- α -2b in the acute period of the disease in the form of rectal suppositories. The comparison group (III) was 30 people who received only pathogenetic and symptomatic therapy in the acute period of the disease.Combined therapy with recombinant interferon α -2b in combination with highly active antioxidants, vitamins E and C (VIFERON®), as rectal suppositories and gel for external use, significantly improved the clinical and laboratory manifestations of the disease and shortened the duration of stay in a hospital not only with group of comparison, but also with patients of group II who received recombinant interferon α -2b (VIFERON®) only in the form of rectal suppositories.The conclusion. The combined use of recombinant interferon α -2b (VIFERON®) in the form of rectal suppositories and gel for external use may be recommended for the treatment of infectious mononucleosis in children.